Recyclable functionalized polymer films for the efficient removal of hexavalent chromium from aqueous solutions. Issue 63 (11th November 2019) - Liu, Weikang; Wang, Mei; Wen, Zhigang; Li, Zhong; Yang, Liang; Jiang, Changlong
Abstract : A PEI-PVA functionalized composite film has been developed to remove hexavalent chromium ion Cr(vi ) from water by an adsorption–reduction mechanism. Abstract : In this study, polyethylenimine-functionalized poly(vinyl alcohol) (PEI-PVA) films were prepared for the first time to remove aqueous Cr(vi ). The results indicate that our PEI-PVA films have an excellent potential for Cr(vi ) removal and their maximum removal capacity was 396.83 mg g −1 . The optimized pH value was 2, the adsorption of Cr(vi ) was fitted to the Langmuir model, and the kinetics of uptake could be described well by a pseudo-second-order rate model. Taking into account the simplified separation method of adsorbents and solutions, we used a PVA film as a carrier in which PEI-PVA microspheres were filled to obtain a PEI-PVA functionalized film (PPF). The PPF shows a great efficiency in the removal of Cr(vi ) ions in solution, which can absorb and reduce the Cr(vi ) ion concentration in the solution in 90 min. PPF has excellent selectivity and the removal efficiency of Cr(vi ) ions in the presence of co-existing ions is not reduced. It also has good recycling properties; the removal efficiency remains at 77% over four cycles. The removal mechanism of Cr(vi ) ions by PEI-PVA microspheres involves the reduction of the adsorbed Cr(vi ) ions to Cr(iii ) ions, which are less toxic.